Prevalence and genomic investigation of Salmonella isolates recovered from animal food-chain in Xinjiang, China. (April 2021) - Liu, Yingyu; Jiang, Jindou; Ed-Dra, Abdelaziz; Li, Xiaomeng; Peng, Xianqi; Xia, Lining; Guo, Qingyong; Yao, Gang; Yue, Min
Graphical abstract: Highlights: Salmonella was detected in 314 of the 2408 samples (13.04%). Six serovars and four serogroups were identified with dominance of Agona and serogroup O:4(B). 92.04%of studied isolates were multi-drug resistance (MDR). We reported the presence of cdtB gene encoding typhoid toxins in four S . Indiana isolates. We demonstrated the use of genomic framework for routine surveillance in China. Abstract: Salmonella is a major foodborne pathogen worldwide, causing serious cases of morbidity and mortality due to the consumption of contaminated foods. Animal-borne foods were considered the main source of transferring Salmonella to humans; however, route surveillance by genomic platforms along the food-chain is limited in China. Here, we proceeded to the application of whole genome sequencing in the epidemiological analysis of Salmonella isolated along the food-chain in Xinjiang, China. A total of 2408 samples were collected from farms, slaughterhouses, and markets, and subjected to the isolation of Salmonella strains. 314 (13.04%) of the samples were positive for Salmonella . Phenotypic antimicrobial resistance was conducted by the broth dilution method using 14 antimicrobial agents belonging to ten classes for all 314 isolates. A selection of representative 103 isolates was subjected to whole-genome sequencing for understanding the Salmonella diversity, including serovars, antimicrobial and virulence genes, plasmid types, multi-locus sequence types, and allelic types. We found that S. Agona was the dominant serovar and O:4(B) was the dominant serogroup. The dominant genotype was ST13 and each serovar has a unique MLST pattern. Plasmids prediction reported Col(MGD2)_1 and Col(Ye4449)_1 as the dominant plasmids, in addition to the detection of IncFII(S)_1 and IncFIB(S)_1 carried by all S . Enteritidis isolates. Importantly, virulence genes prediction showed the presence of cdtB gene encoding typhoid toxins, spv genes, and pef gene cluster encoding fimbriae in the genomes of S . Indiana and S . Enteritidis. Phenotypic antimicrobial resistance identified 92.04% of the sampled isolates as multi-drug resistance (MDR), with high resistance to tetracycline (78.03%; 245/314), amoxicillin/ clavulanic acid (75.80%; 238/314), and ampicillin (70.70%; 222/314). Together, we firstly reported the prevalence of MDR Salmonella isolates harboring critical virulence factors transmission via animal-borne food-chain in Xinjiang, hence route surveillance by whole-genome sequencing platform could facilitate recognition and project early warning for the emerging MDR clones along the food-chain.